PENINGKATAN KESADARAN MASYARAKAT TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA LUBUK BATANG LAMA KABUPATEN OGAN KOMERING ULU SUMATERA SELATAN - Irsan, Irsan; utama, meria; laili, yunial (Jurnal Atma Inovasia, 2022)
The implementation of Corporate Social Responsibility (CSR) in the field of natural resources varies in each region. Especially in the Lubuk Batang Lama Village area, the CSR activities carried out are still relatively small. For this reason, it is necessary for the community to be given an understanding of good communication mechanisms in carrying out CSR activities between the three partners (Mining Companies, Community and Local Governments). As well as the active efforts of the community to be involved together in CSR programs in the Lubuk Batang Lama Village area. With this counseling, it is hoped that the community can plan their regional development by designing CSR programs that are directly related to the interests of the community.